PENGARUH PEMBERIAN AIR REBUSAN DAUN SELEDRI TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - La Ode Alifariki; Wa Ode Salma (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a wellrested state. Hypertension control can be done with a pharmacological approach and nonpharmacological. One of the non-pharmacological treatments is to use celery. The purpose of this study was to determine the effect of celery leaf stew on blood pressure in patients with hypertension This research is limited from 2009 to 2022 and gets 8 eligible articles sourced from the Google Scholar search engine with the keywords “celedry, blood pressure AND hypertension. The results of the study reported that from 8 articles it was found that celedry was effective in lowering blood pressure in patients with hypertension.